Neurogenesis in the adult brain I neurobiology - Seki, Tatsunori; Sawamoto, Kazunobu; Parent, Jack M.; Alvarez-Buylla, Arturo; SpringerLink (Online service). (Tokyo, Japan Springer, 2011)
The discovery of adult neurogenesis caused a paradigm shift in the neurosciences. For more than 100 years, it was believed that adult neurons do not regenerate. Joseph Altman and Fernando Nottebohm found proof to the contrary and changed the course of history. Their research, included here, provides the foundations of the field. Today, adult neurogenesis is a rapidly expanding discipline applicable to the study of brain development and diseases, learning and memory, aging, and neuropsychiatric disorders. With multiple authors, the 27 chapters of this book contain the latest work in two volumes. The first presents the basic biology of adult neurogenesis in non-mammalian vertebrates and in the mammalian hippocampus and olfactory bulb, and the second discusses clinical implications and delves into adult neurogenesis and brain injury as well as neurodegenerative and neuropsychiatric pathologies. With details of the anatomy, physiology, and molecular biology of the two neurogenic brain regions, this book provides indispensable knowledge for many areas of neuroscience and for experimental and clinical applications of adult neurogenesis to brain therapy.
Neurogenesis in the Adult Brain I; Preface; Contents; Contents of Volume II; Contributors; Part I: History; Chapter 1: The Discovery of Adult Mammalian Neurogenesis*; Chapter 2: Song Learning in Birds Offers a Model for Neuronal Replacement in Adult Brain; Part II: Basic Aspects of Neurogenesis; Chapter 3: Fate Specification of Neural Stem Cells; Chapter 4: Fractones: Home and Conductors of the Neural Stem Cell Niche; Part III: Adult Neurogenesis in Non-mammalian Vertebrates; Chapter 5: Adult Neurogenesis in Teleost Fish; Chapter 6: Adult Neurogenesis in Reptiles Part IV: Adult Neurogenesis in the HippocampusChapter 7: From Embryonic to Adult Neurogenesis in the Dentate Gyrus; Chapter 8: Activity-Dependent Regulation of the Early Phase of Adult Hippocampal Neurogenesis; Chapter 9: Integration of New Neurons into the Adult Hippocampus; Chapter 10: Adult Neurogenesis in the Hippocampus: Lessons from Natural Populations; Chapter 11: Regulation of Adult Neurogenesis by Environment and Learning; Part V: Adult Neurogenesis in the Olfactory Bulb; Chapter 12: Epithelial Organization of Adult Neurogenic Germinal Niches Chapter 13: Neurogenesis in the Adult Rabbit: From Olfactory System to CerebellumChapter 14: Neuronal Migration in the Adult Brain; Chapter 15: Development and Survival of Adult-Born Olfactory Neurons; Chapter 16: Wiring New Neurons with Old Circuits; Chapter 17: Control of Adult-Born Neuron Production by Converging GABA and Glutamate Signals; Index
Electronic reproduction.
Keywords: Neurons -- Growth; Brain -- Cytology; Brain -- Molecular aspects; Electronic books